Vehicle gearbox dynamics: centre distance influence on mesh stiffness and spur gear dynamics - V. Skrickij; M. Bogdevičius (Transport, 2010)
Vehicle gearbox dynamics is characterized by time varying mesh stiffness. The paper presents a survey of methods used for determining mesh stiffness and the analysis of the centre distance influence on it. The refined mathematical transmission model presenting the centre distance as a variable is presented. The centre distance error as well as backlash and bearing flexibility is defined and the influence of these factors on mesh stiffness and spur gear dynamics is investigated. The results obtained from this paper may be used in gear-box diagnostics.